Distance learning tools preferences: among office management lecturers (UiTM Pahang) / Rozita Mengen and Nor Farhana Mohd Azmi - Mengen, Rozita; Mohd Azmi, Nor Farhana (2022)
This study is about discovering the most preferred teaching tools amongst selected lecturers during the Open Distance Learning (ODL) exercise due to COVID-19 Pandemic starting from the early 2020 through the early 2022 and the reason behind the preferences. Base on the findings it was discovered that Google Meet is the most favored tool used followed by WhatsApp.